Games in code form versus games in extensive form - Peixoto, C.; Ferreira, M. A. M. (Proceedings of the International Conference Quantitative Methods in Economics (Multiple Criteria Decision Making XI), 2002)
The idea of a new game representation occurred when we analysed a game with 3 players in the normal form. It seemed that a representation that gave us a global picture of the game would be the ideal. As a consequence of this idea, we were tried a game representation that agglutinated the information of extensive form and of normal form. We imagined the codified representation and we verified that this representation has great advantages when the number of players is greater or equal than 3 , when the game is an imperfect information one and mainly when it is sequential. We present the code form comparing that representation with the extensive representation.